1993
DOI: 10.1007/bf00015973
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and analysis of a cDNA coding for the bifunctional dihydrofolate reductase-thymidylate synthase of Daucus carota

Abstract: Molecular cloning of dihydrofolate reductase-thymidylate synthase (DHFR-TS) of Daucus carota was achieved by immunoscreening of a cDNA library obtaining a 2 kbp clone which contains an open reading frame of 1528 bp. Comparison of the deduced amino acid sequence with those from other sources revealed the presence of motifs typical of DHFR and TS thus confirming the bifunctional nature of the carrot protein. As in other organisms, a higher degree of conservation was observed in the TS domain. Analysis of the dhf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Our studies strengthen the idea of a crucial role for DHFR in the reduction of dihydrofolate produced by oxidation of THF by TS activity. In plants, including Arabidopsis, DHFR and TS are encoded by bifunctional genes coding for bifunctional polypeptides (Lazar et al, 1993;Luo et al, 1993Luo et al, , 1997Wang et al, 1996). The direct channeling of dihydrofolate between the TS and DHFR domains in bifunctional polypeptides has been proposed (Knighton et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Our studies strengthen the idea of a crucial role for DHFR in the reduction of dihydrofolate produced by oxidation of THF by TS activity. In plants, including Arabidopsis, DHFR and TS are encoded by bifunctional genes coding for bifunctional polypeptides (Lazar et al, 1993;Luo et al, 1993Luo et al, , 1997Wang et al, 1996). The direct channeling of dihydrofolate between the TS and DHFR domains in bifunctional polypeptides has been proposed (Knighton et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Like in protozoa, plant DHFR exists as a bifunctional enzyme coupled with thymidylate synthase (TS) (Luo et al, 1993; Neuburger et al, 1996; Cox et al, 1999), or as a monofunctional enzyme coupled with TS as a part of a multimeric complex (Toth et al, 1987). In bacteria, yeast and vertebrates, DHFR is a monofunctional enzyme.…”
Section: Folate Biosynthesis In Plantsmentioning
confidence: 99%
“…In two cases (Bachmann andFollmann 1987, Cella et al 1988), bifunctional DHFR-TS activities were localized on the same monomer and almost always native enzyme is formed by more than one subunit. Evidence of the bifunctionality of one of the carrot enzymes (Cella et al 1988) has been strengthened by sequencing of two oligopeptides obtained by tryptic digestion of the 58 kDa monomer, which contain, respectively, sequences similar to those found at active sites of DHFR and TS from bacteria and mammalians (Cella et al 1991a) and by the isolation of a cDNA coding for the bifunctional polypeptide (Luo et al 1993). It should be noted that the 58 kDa bifunctional monomer purified in domesticated carrot was found also in wiid carrot (A. Baiestrazzi, M. Branzoni, D. Carbonera, B. Parisi and R. Cella, unpublished data), whereas Toth et al (1987) found a polyfunctional complex with DHFR and TS activities on different monomers.…”
Section: Dihydrofolate Reductase and Thymidylate Synthase In Plantsmentioning
confidence: 99%
“…Until recently the unavailability of a DNA probe for plant DHFR has prevented demonstration that overproduction of the target enzyme observed in several cell lines selected for MTX-resistance could actually be due to gene amplification. The use of two different approaches has now ied to construction of carrot dhfr-ts probes (Piffanelli et al 1991, Luo et al 1993). In one case, a family of oligonucleotides (containing inosine) were synthesized on the basis of the sequence of the decapeptide TWESIPIQHR, obtained by tryptic digestion of carrot DHFR-TS, corresponding to the dihydrofolate-binding site in the domain where also MTX binds.…”
Section: Molecular Studies On Ptant Dihydrofolate Reductase and Thymimentioning
confidence: 99%